2019
DOI: 10.21638/11701/spbu08.2019.402
|View full text |Cite
|
Sign up to set email alerts
|

Gamification: Main approaches to definition and research directions

Abstract: Таблица 2. Распределение статей по журналам, представленным в списке ABS Категория и название журнала Количество статей Журналы категории А, в том числе:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…Some brands to get to value co-creation stage of relationship faster are using intensive gamification [Leclercq, Hammedi, Poncin, 2018]. Discussion of gamification intensity is very fragmented despite the issue with the definition of concept boundaries [Werbach, 2014;Muravskaia, Smirnova, 2019]. In early studies researchers suggested to adopt the same approach to gamification classification as it used in game research: hard fun, easy fun, people fun, serious fun [Lazarro, 2009], which has been used to develop a typology of behavior in game-like environment, known as Hexad model [Tondello et al, 2019].…”
Section: The Role Of Gamification In Customer Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Some brands to get to value co-creation stage of relationship faster are using intensive gamification [Leclercq, Hammedi, Poncin, 2018]. Discussion of gamification intensity is very fragmented despite the issue with the definition of concept boundaries [Werbach, 2014;Muravskaia, Smirnova, 2019]. In early studies researchers suggested to adopt the same approach to gamification classification as it used in game research: hard fun, easy fun, people fun, serious fun [Lazarro, 2009], which has been used to develop a typology of behavior in game-like environment, known as Hexad model [Tondello et al, 2019].…”
Section: The Role Of Gamification In Customer Engagementmentioning
confidence: 99%
“…The proposed classification is based on conclusions derived from literature analysis and comparison of main research questions which are posed in articles dedicated to gamification [Muravskaia, Smirnova, 2019] with a clear focus on customer engagement and its analysis with the help of bibliometric tools. At this stage classification is more conceptual, however, it can be already used for introducing additional segmentation criteria.…”
Section: Gamificationmentioning
confidence: 99%